Autonomy, sociopolitical passion and recycling in the poetic “I” of both Walt Whitman and César Vallejo - Ambroggio, Luis Alberto (Espergesia, 2017)
This article aims to establish the similarity and influence, both in the discursive axes and in the aesthetic characteristics that exist between Vallejo’s and Whitman’s poetry in which the poetic “I” of both is universal, inclusive and caring. They are concerned about the human condition directed to the search for freedom, but not only as an instrument of creativity but also in the search for a better world. It is claimed that Vallejo expresses his socio-political pain and caring with a revolutionary aesthetic, influenced by Whitman’s democratic aesthetic. Likewise, both bards denote a vitalistic aesthetic and show it in the rupture of grammar in order to broaden its capacity for expression. In conclusion, the similarity between the two poets has been demonstrated as well as Whitman’s influence in Vallejo.